Oral health status, behaviours, food and beverage consumption of aboriginal children in Australia. (16th May 2020) - George, Ajesh; Villarosa, Amy R.; Ingram, Suzanne; Fatema, Kaniz; Elliott, Koby; Grace, Rebekah; Kemp, Lynn; Scharkie, Sheryl; Anderson, Cheryl; Bucknall, Natasha; Wright, Darryl C.; Comino, Elizabeth
Abstract: Issue addressed: Dental decay is prevalent among Australian Aboriginal children, yet little is known about their oral health‐related behaviours. This study explored the oral health status, behaviours, food and beverage consumption of Aboriginal school children aged 7‐9 years in Sydney, Australia. Methods: Parents who were part of an existing longitudinal birth cohort ("Gudaga") were surveyed when their child was between 7 and 9 years. Children (n = 110) also received oral health screening by a trained nurse. Results: A number of children (62%–91%) had at least one visible oral health problem across the 2 years. Around two thirds (62%–67%) of parents rated their child's oral health as excellent/very good and less than half the children (32%–45%) had received dental check‐ups. Most children (79%–90%) brushed their teeth and drank water (97%) but more than half (57%–70%) also drank sugar sweetened beverages daily. Conclusions: Parents are instilling good oral health behaviours, however, the oral health screening suggests children are experiencing oral health issues of which parents may be unaware. Parents also seem to be unaware of beverage consumption practices that can increase the risk of childhood decay. So what?: The findings highlight the need for greater oral health awareness among Aboriginal families on how to recognise early symptoms dental decay and risk factors like sugar sweetened beverages among school going children. This suggests that existing health promotion strategies may not be reaching many Aboriginal families in the urban areas and more culturally appropriate programs may be needed.